Strange Bedfellows An experiment in Student-directed Interdisciplinary Research - de Ruiter, Naomi; Wittingslow, Ryan; Chiu, Roland (University College Groningen, 2024)
'Interdisciplinarity' is a bit of a buzzword in the Dutch university sector. It is also one of the most prioritized policy goals at a national and European level. Yet, 'interdisciplinarity' remains under-defined, and the challenges and obstacles unique to doing interdisciplinarity remain fuzzy. How, then, are we supposed to adopt an interdisciplinary approach if we don't even know what the word means? In this peer-reviewed edited volume of student scholarship, we delve into what it means to do interdisciplinarity in response to this challenge. Drawing upon both the disciplinary expertises of professional researchers and educators, and the experiences and analyses of students actually enrolled in interdisciplinary programmes, this volume is unique in offering both high-level conceptual analyses of the virtues and problems inherent to interdisciplinary research, and on-the-ground case notes of what interdisciplinary teaching and research looks like in practice.